Inscribed Circles

Geometry Level pending

In A B C \triangle{ABC} , the inscribed circle with radius r r is tangent to A B , B C \overline{AB}, \overline{BC} and A C \overline{AC} at points D , E D, E and F F respectively.

Folding the arc of the semi-circle at a right angle, as shown below, the radius of the semicircle becomes the height of the tetrahedron.

If A A B C = 2 r ( 2 r + 2 ( 2 1 ) ) A_{\triangle{ABC}} = 2r(2r + 2(\sqrt{2} - 1)) and the volume V T V_{T} of the tetrahedron can be expressed as V T = α β β ( α 1 ) β V_{T} = \dfrac{\alpha^{\beta}}{\beta}(\sqrt{\alpha} - 1)^{\beta} , where α \alpha and β \beta are coprime positive integers, find α + β \alpha + \beta .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Dec 27, 2020

Let the center of the inscribed circle be I I and let θ = I C F = I C E \theta = \angle ICF = \angle ICE . Then from I C E \triangle ICE , I C = ( r + 1 ) 2 + r 2 = 2 r 2 + 2 r + 1 IC = \sqrt{(r + 1)^2 + r^2} = \sqrt{2r^2 + 2r + 1} , cos θ = r + 1 2 r 2 + 2 r + 1 \cos \theta = \cfrac{r + 1}{\sqrt{2r^2 + 2r + 1}} , sin θ = r 2 r 2 + 2 r + 1 \sin \theta = \cfrac{r}{\sqrt{2r^2 + 2r + 1}} , and cos 2 θ = cos 2 θ sin 2 θ = ( r + 1 ) 2 r 2 2 r 2 + 2 r + 1 = 2 r + 1 2 r 2 + 2 r + 1 \cos 2\theta = \cos^2 \theta - \sin^2 \theta = \cfrac{(r + 1)^2 - r^2}{2r^2 + 2r + 1} = \cfrac{2r + 1}{2r^2 + 2r + 1} .

As tangents from the same point, C F = C E = r + 1 CF = CE = r + 1 , B D = B E = r + 2 2 3 BD = BE = r + 2\sqrt{2} - 3 , and x = A F = A D x = AF = AD . Therefore, the perimeter of A B C \triangle ABC is P = 2 ( r + 1 ) + 2 ( r + 2 2 3 ) + 2 x P = 2(r + 1) + 2(r + 2\sqrt{2} - 3) + 2x , and the semiperimeter is s = 2 r + 2 2 2 + x s = 2r + 2\sqrt{2} - 2 + x .

Since A A B C = 2 r ( 2 r + 2 ( 2 1 ) ) A_{\triangle ABC} = 2r(2r + 2(\sqrt{2} - 1)) and A A B C = r s = r ( 2 r + 2 2 2 + x ) A_{\triangle ABC} = rs = r(2r + 2\sqrt{2} - 2 + x) , these equations combine and solve to x = 2 r + 2 2 2 x = 2r + 2\sqrt{2} - 2 .

The sides of A B C \triangle ABC are then A B = 2 r + 2 2 2 + r + 2 2 3 = 3 r + 4 2 5 AB = 2r + 2\sqrt{2} - 2 + r + 2\sqrt{2} - 3 = 3r + 4\sqrt{2} - 5 , A C = 2 r + 2 2 2 + r + 1 = 3 r + 2 2 1 AC = 2r + 2\sqrt{2} - 2 + r + 1 = 3r + 2\sqrt{2} - 1 , and B C = r + 2 2 3 + r + 1 = 2 r + 2 2 2 BC = r + 2\sqrt{2} - 3 + r + 1 = 2r + 2\sqrt{2} - 2 .

Then by the law of cosines on A B C \triangle ABC , cos 2 θ = ( 3 r + 2 2 1 ) 2 + ( 2 r + 2 2 2 ) 2 ( 3 r + 4 2 5 ) 2 2 ( 3 r + 2 2 1 ) ( 2 r + 2 2 2 ) = r 2 2 + 5 3 r + 2 2 1 \cos 2\theta = \cfrac{(3r + 2\sqrt{2} - 1)^2 + (2r + 2\sqrt{2} - 2)^2 - (3r + 4\sqrt{2} - 5)^2}{2(3r + 2\sqrt{2} - 1)(2r + 2\sqrt{2} - 2)} = \cfrac{r - 2\sqrt{2} + 5}{3r + 2\sqrt{2} - 1} .

That means cos 2 θ = 2 r + 1 2 r 2 + 2 r + 1 = r 2 2 + 5 3 r + 2 2 1 \cos 2\theta = \cfrac{2r + 1}{2r^2 + 2r + 1} = \cfrac{r - 2\sqrt{2} + 5}{3r + 2\sqrt{2} - 1} , which rearranges to ( r 1 ) ( r + 2 1 ) 2 = 0 (r - 1)(r + \sqrt{2} - 1)^2 = 0 and solves to r = 2 1 r = \sqrt{2} - 1 for r > 0 r > 0 .

Therefore, V T = 1 3 A A B C r = 1 3 2 r ( 2 r + 2 ( 2 1 ) ) r = 2 3 3 ( 2 1 ) 3 V_T = \frac{1}{3} \cdot A_{\triangle ABC} \cdot r = \frac{1}{3} \cdot 2r(2r + 2(\sqrt{2} - 1)) \cdot r = \cfrac{2^3}{3}(\sqrt{2} - 1)^3 , so α = 2 \alpha = 2 , β = 3 \beta = 3 , and α + β = 5 \alpha + \beta = \boxed{5} .

Rocco Dalto
Dec 27, 2020

I actually did the problem in general to obtain r = 2 1 r = \sqrt{2} - 1 , so I will present the way I actually did it.

Let a = 2 2 3 a = 2\sqrt{2} - 3 and b = 1 b = 1 .

A A B C = 1 2 ( 2 x + 4 r + 2 ( a + b ) ) = ( x + 2 r + a + b ) r A_{\triangle{ABC}} = \dfrac{1}{2}(2x + 4r + 2(a + b)) = (x + 2r + a + b)r

Using Heron's formula with s = x + 2 r + a + b s = x + 2r + a + b \implies

A A B C = ( x + 2 r + a + b ) ( r + a ) ( r + b ) x A_{\triangle{ABC}} = \sqrt{(x + 2r + a + b)(r + a)(r + b)x} \implies

( x + 2 r + a + b ) 2 r 2 = ( x + 2 r + a + b ) ( r + a ) ( r + b ) x (x + 2r + a + b)^2 r^2 = (x + 2r + a + b)(r + a)(r + b)x \implies

r 2 x = ( 2 r + a + b ) r 2 = ( r 2 + ( a + b ) r + a b ) x r^2x = (2r + a + b)r^2 = (r^2 + (a + b)r + ab)x \implies

( ( a + b ) r + a b ) x = ( 2 r + a + b ) r 2 x = ( 2 r + a + b ) r 2 ( a + b ) r + a b ((a + b)r + ab)x = (2r + a + b)r^2 \implies x = \dfrac{(2r + a + b)r^2}{(a + b)r + ab}

A A B C = ( 2 r + a + b ) ( r 2 ( a + b ) r + a b + 1 ) r = \implies A_{\triangle{ABC}} = (2r + a + b)(\dfrac{r^2}{(a + b)r + ab} + 1)r =

( 2 r + a + b ) ( r 2 + ( a + b ) r + a b ) r ( a + b ) r + a b = 2 ( 2 r + a + b ) r \dfrac{(2r + a + b)(r^2 + (a + b)r + ab)r}{(a + b)r + ab} = 2(2r + a + b)r \implies

r 2 + ( a + b ) r + a b = 2 ( a + b ) r + 2 a b r 2 ( a + b ) r a b = 0 r^2 + (a + b)r + ab = 2(a + b)r + 2ab \implies r^2 - (a + b)r - ab = 0

Letting a = 2 2 3 a = 2\sqrt{2} - 3 and b = 1 b = 1 \implies r 2 2 ( 2 1 ) r ( 2 2 3 ) = 0 r = 2 1 r^2 - 2(\sqrt{2} - 1)r - (2\sqrt{2} - 3) = 0 \implies r = \sqrt{2} - 1 \implies

A A B C = 8 ( 2 1 ) 4 3 2 2 = 8 ( 2 1 ) 2 A_{\triangle{ABC}} = \dfrac{8(\sqrt{2} - 1)^4}{3 - 2\sqrt{2}} = 8(\sqrt{2} - 1)^2 \implies

8 3 ( 2 1 ) 3 = 2 3 3 ( 2 1 ) 3 = α β β ( α 1 ) β \dfrac{8}{3}(\sqrt{2} - 1)^3 = \dfrac{2^3}{3}(\sqrt{2} - 1)^3 = \dfrac{\alpha^{\beta}}{\beta}(\sqrt{\alpha} - 1)^{\beta} \implies α + β = 5 \alpha + \beta = \boxed{5} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...